Immunization With Outer Membrane Vesicles Derived From Major Outer Membrane Protein-Deficient Salmonella Typhimurium Mutants for Cross Protection Against Salmonella Enteritidis and Avian Pathogenic Escherichia coli O78 Infection in Chickens - Chen, Yuxuan; Jie, Kaiwen; Li, Biaoxian; Yu, Haiyan; Ruan, Huan; Wu, Jing; Huang, Xiaotian; Liu, Qiong (Frontiers in Microbiology, 2020)
Colibacillosis is an economically important infectious disease in poultry, caused by avian pathogenic Escherichia coli (APEC). Salmonella enterica serovar Enteritidis (S. Enteritidis) is a major cause of food-borne diseases in human circulated through poultry-derived products, including meat and chicken eggs. Vaccine control is the mainstream approach for combating these infections, but it is difficult to create a vaccine for the broad-spectrum protection of poultry due to multiple serotypes of these pathogens. Our previous studies have shown that outer membrane vesicles (OMVs) derived from Salmonella enterica serovar Typhimurium mutants with a remodeled outer membrane could induce cross-protection against heteroserotypic Salmonella infection. Therefore, in this study, we further evaluated the potential of broad-spectrum vaccines based on major outer membrane protein (OMP)-deficient OMVs, including ΔompA, ΔompC, and ΔompD, and determined the protection effectiveness of these candidate vaccines in murine and chicken infection models. The results showed that ΔompA led to an increase in the production of OMVs. Notably, ΔompAΔompCΔompD OMVs showed significantly better cross-protection against Salmonella enterica serovar Choleraesuis, S. Enteritidis, APEC O78, and Shigella flexneri 2a than did other omp-deficient OMVs, with the exception of ΔompA OMVs. Subsequently, we verified the results in the chicken model, in which ΔompAΔompCΔompD OMVs elicited significant cross-protection against S. Enteritidis and APEC O78 infections. These findings further confirmed the feasibility of improving the immunogenicity of OMVs by remodeling the outer membrane and provide a new perspective for the development of broad-spectrum vaccines based on OMVs.